Jabbar K. Abdul-Hassan Synergistic effects of various acidity and salinity levels on survival juveniles of two fish carps (Cyprinus carpio L. and Ctenopharyngodon idella Val.) during exposure for 96 hrs. - Jabbar Abdul-Hassan (University of Thi-Qar Journal of Science, 2019)
The effects of extreme acidity and salinity on survival of juveniles for two carp species common carp (Cyprinus carpio L.) and grass carp (Ctenopharyngodon idella Val.) were investigated. The juveniles were exposed to five different degrees of acidities (6.4, 5.8, 5.2, 4, 3.4),and the control waters with 7.6 pH & 1.03 S‰. The second experiments was conducted by using two different salinities (Low = 0.09 ‰ and High=20.5‰) during 96 hrs.The result statistical analyses (by using SPSS program) were showed that the juveniles of Cyprinus carpio were less resistant to different acidity values compared with Ctenopharyngodonidella. The LC50 pH values were 6.1 and 6 for common carp and grass carp respectively, but in thecase of synergistic effects showed that Cyprinus carpio have more resistance than Ctenopharyngodon idella, their LC50 pH values were 4 (at low S‰), 5.35 (at high S‰), and 5.2  (low S‰), 5.5(at high S‰) respectively.